On pairwise super continuous mappings in bitopological spaces - F. H. Khedr; A. M. Al-Shibani (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to define and study super-continuous mappings and some other forms of continuity such as strong continuity, perfect continuity and complete continuity in bitopological spaces and investigate the relations between these kinds of continuity and their effects on some kinds of spaces.